Fundação Dom José Maria Pires: uma experiência de educação popular -Serra Redonda-PB - Silva Junior, Carlos Augusto da (2014)
This research aimed to examine the experience of popular education experienced within the formative process of Dom José Maria Pires Foundation, located in Serra Redonda -Paraiba -Brazil. It is to understand the challenges of the training process carried out by youth and adults of the popular media, as well as by their teachers / educators, from the period of (2000-2013) that corresponded to the latest stage of this training experience.Regarding the specific goals we list: understanding the relationship of Don José Maria Pires Foundation with the Roman Catholic Church; see the influence of Liberation Theology andthe Theology of Hoe in the educational practices of Don José Maria Pires Foundation; analyze the course of Popular Educators offered by Don José Maria Pires Foundation in light of the Freire s contributions.We resort to the concept of memory in Bosi (1994), Ferreira (2000), Halbwachs (2003), Le Goff (2003) and Nora (1993), popular education Brandão (1981) and (2006), Freire (1998), FreireandNogueira (1991), Melo Neto (2004), Draft (2008), among others.Regarding the methodology, we use a qualitative approach, through oral history, in their thematic perspective, which allowed us to analyze the testimonies of the protagonists of this educational process (teachers and students), besidesthe documentary research in which we concentrate on institution achieve, their minutes and their courseplans, theirvideos and textbooks, the brochures, newspapers and magazine of the era who recorded historical facts, the blog of the Foundation and the photographs that record their most important moments.This research allowed us to conclude that the experience led by the FDJMP contributed significantly to the Popular Education for offering systematic training guided by theoretical and methodological elements derived of epistemological constructs of popular education in Freire's perspective with significant contributions from methodological praxis of Theology of Hoefrom Fr. José Comblin and other employees.